2017
DOI: 10.3390/nano7090274
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Titania Nanotube Coatings Enriched with Silver Nanograins by Chemical Vapor Deposition

Abstract: Bioactivity investigations of titania nanotube (TNT) coatings enriched with silver nanograins (TNT/Ag) have been carried out. TNT/Ag nanocomposite materials were produced by combining the electrochemical anodization and chemical vapor deposition methods. Fabricated coatings were characterized by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. The release effect of silver ions from TNT/Ag composites immersed in bodily fluids, has been studied using inductively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 64 publications
5
46
0
Order By: Relevance
“…8 ± 1.5 nm. The part of the above-mentioned coatings was enriched with AgNPs using the CVD technique [27][28][29][30]. According to the results of our previous works, the AgNPs filled the interiors of the TNT5 nanoporous layer ( Figure 1g) while in the case of TNT15, the spherical nanoparticles of diameters c.a.…”
Section: Ti6al4v Implants Modified By Titania Nanotube Coatingsmentioning
confidence: 85%
See 4 more Smart Citations
“…8 ± 1.5 nm. The part of the above-mentioned coatings was enriched with AgNPs using the CVD technique [27][28][29][30]. According to the results of our previous works, the AgNPs filled the interiors of the TNT5 nanoporous layer ( Figure 1g) while in the case of TNT15, the spherical nanoparticles of diameters c.a.…”
Section: Ti6al4v Implants Modified By Titania Nanotube Coatingsmentioning
confidence: 85%
“…Serious medical problems associated with the introduction of implants to the human body are infections, which can lead to increased patients failure and mortality [68][69][70][71]. To solve this problem, the implant surface is modified by the formation of bioactive nanostructures (e.g., TiO 2 nanotubes, nanofibers) and/or their enrichment with metal nanoparticles (mainly silver and copper) [20,27,28,[72][73][74]. In our previous study it has been shown that TiO 2 nanotubes formed on titanium alloy (Ti6Al4V), in particular the coatings obtained using low-potential anodic oxidation, possessed in vitro anti-biofilm activity tested on S. aureus model [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations